Catalytic wet air oxidation of linear alkylbenzene sulphonate - Abu Hassan, Mohd. Ariffin; Metcalfe, Ian S. (Faculty of Chemical and Natural Resources Engineering, UTM, 2007)
In view of slow rates of wet oxidation process, the catalytic oxidation of organic containing wastewaters over various homogenous and heterogenous catalysts has received a lot of attention. The impact of heterogenous catalysts on the Wet Air Oxidation (WAO) of Linear Alkylbenzene Sulphonate (LAS) has been determined. Experiments were carried out at temperatures from 180C to 220C for 120 minutes, and an oxygen partial pressure of 1.5MPa was maintained for all the experiments. The catalyst was introduced to the original solution of LAS and all of the catalysts were used in a powder form. WAO of LAS in the presence of heterogenous catalysts increased the TOC and COD removals. CuO.ZnO/Al2O3 was found to be the effective catalyst for the degradation of LAS and this catalyst were capable of oxidising VFAs which were resistant to further oxidation during uncatalysed WAO. Desulphonation did occur in the presence of Pt/Al2O3 and CuO.ZnO/Al2O3. Leaching of both copper and zinc occured during the CuO.ZnO/Al2O3 catalysed WAO. It was found that within the range of experimental conditions studied, the homogenous activity of leached metals is insignificant and therefore, the role of heterogenous activity of CuO.ZnO/Al2O3 is still dominant.